EFL students’ empowerment using servant leadership: a look through the lens of students in Afghanistan - Rohullah Yousofi; Fatemeh Rahimzad (Cogent Education, 2024)
AbstractIn recent years, many studies have paid attention to servant leadership in different fields and occasions, yet few studies have paid attention to higher education in Afghanistan. The current explanatory study examined to what extent university teachers use the four principles of servant leadership (empathy, awareness, conceptualization and foresight) in EFL classrooms and investigated the effects of each principle on EFL students’ development and learning. This study used a mixed-method technique, collecting data from 116 students through a questionnaire and 9 students via semi-structured interviews. Both sets of findings indicated that all EFL teachers mostly have used the four principles of servant leadership in their instructions and classrooms. Also, inferential statistics unveiled that no robust difference exists between students’ reported experiences of their teachers’ use of servant leadership principles and various genders and years of schooling. Besides, qualitative findings revealed that the implementation of those principles has had some impacts and effects on students’ empowerment and learning development. The positive points were motivation, encouragement, a sense of care, a sense of belonging and engagement in learning. However, the limitations observed were that some teachers consistently differentiated between less engaged and more capable students during class activities, and they provided limited support for students to overcome challenges. Furthermore, the study offered some pedagogical implications such as promoting servant leadership principles through conducting short capacity-building workshops and establishing leadership centers at campuses.